Feminine Honor May be More Than Sexual Purity and Familiar Obligation: A Review of the Literature - Nelsen, Emily P. (Kansas State University. K-State Libraries, 2016)
The published research appears to indicate a consensus among researchers and scholars that feminine honor has so far been defined as a woman’s reputation that is created and maintained through sexual purity and familiar obedience. This essay critically examines the past literature on honor beliefs in order to evaluate the extent to which this consensus is accurate. Though some of the evidence from culture of honor and masculine honor research may support this definition, because it does not ask directly about feminine honor this conclusion may be inaccurate. Indeed, in analyzing and integrating the past literature on honor from across fields, it is seen that the current conceptualization is not completely representative of all of the ways in which women may and do become honorable.
Kirmser Undergraduate Research Award - Individual Non-Freshman, honorable mention
Citation: Nelsen, E. (2016) Feminine Honor May be More Than Sexual Purity and Familiar Obligation: A Review of the Literature. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Feminine Honor; Gender; Heternormativity